Children's Productive Use of Academic Vocabulary. Issue 1 (2nd January 2017) - Ma, Shufeng; Zhang, Jie; Anderson, Richard C.; Morris, Joshua; Nguyen-Jahiel, Kim Thi; Miller, Brian; Jadallah, May; Sun, Jingjing; Lin, Tzu-Jung; Scott, Theresa; Hsu, Yu-Li; Zhang, Xin; et al.
Abstract : Instructional influences on productive use of academic vocabulary were investigated among 460 mostly African American and Latina/o fifth graders from 36 classrooms in eight public schools serving low-income families. Students received a 6-week unit on wolf management involving collaborative group work (CG) or direct instruction (DI). The big question that students tried to answer during the unit was whether a community should be permitted to destroy a pack of wolves. In an individual oral interview about an analogue to the wolf question, whether whaling should be allowed, both CG and DI students used more general and domain-specific academic vocabulary from the Wolf Unit than uninstructed control students. CG students used more general academic vocabulary in the whale interview than DI students, and this was mediated by the CG students' greater use of general academic vocabulary in classroom dialogue during the Wolf Unit. These results suggest that CG is an effective instructional approach to promote acquisition and productive use of academic vocabulary for children from underserved communities.